“Negroes of the Crown”: The Management of Slaves Forfeited by Grenadian Rebels, 1796–1831 - Kesselring, K. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2011)
This paper examines how British officials dealt with and disposed of one group of Crown slaves — those forfeited by the Grenadian rebels of 1795-1796 — from their acquisition through to the emancipation of Crown slaves in 1831. Building upon the work of Alvin O. Thompson and Nicholas Draper in particular, it suggests that looking at the treatment of Crown slaves, and specifically at the disposition of slaves acquired through forfeiture, can provide a new vantage point on why emancipation happened when and as it did. Treasury Office documents produced in the course of suits and petitions from individuals who hoped to obtain rights to these enslaved people, as well as correspondence with the local manager of the plantations, demonstrate the tenor and tenacity of the belief that slaves constituted a legitimate form of property. The 1833 decision to compensate slave owners thus appears not simply a matter of pragmatic political compromise and but also a measure consistent with practices and preconceptions that had prevailed in government circles for some years.